"One among many"? Relational panopticism and negotiating non-monogamies. (June 2019) - Willis, Abbey S
Drawing on qualitative in-depth interviews with people in the USA who have formed consensually non-monogamous relationships, this article introduces the term relational panopticism and uses empirical data to demonstrate the theoretical concept. Three primary themes in the data illustrate the origin, expression, and enforcement of relational panopticism: (1) encounters with institutions; (2) encounters with personal networks; and (3) coping and resistance strategies. Focusing on the daily reproduction of compulsory monogamy and the ways in which people in non-monogamous relationships negotiate and resist that reproduction, this study reveals how marginalized romantic and sexual relationship configurations are received and negotiated in interaction with family, peer groups, and institutions.